Beyond stock stories and folktales African Americans' paths to STEM fields - Frierson, Henry T. (Henry Taylor), 1944-; Tate, William; Lloyd-Jones, Brenda; Jean-Marie, Gaetane (Bingley, U.K. : Emerald, 2011)
Historically, women of color have experienced discrimination based on the double jeopardy of race and/or ethnicity, and gender in their quest for access and advancement in higher education. Todays women of color in higher education however are the beneficiaries of courageous and committed women predecessors who confronted and disrupted institutions to attain a higher level of education (Jean-Marie, 2005). This two-edited volume focuses on African American, Hispanic American, Native American, and Asian-Pacific American women whose increased presence in senior level administrative and academic positions in higher education is transforming the political climate to be more inclusive of women of color. Topics include trends and issues, leadership styles/characteristics, tenure and promotion, mentoring/social networks, and challenges and opportunities. As a conceptual framework, the collection of chapters in the two volumes acquaints readers with a broad overview of the characteristics and experiences of women of color in higher education. The two volumes include: Women of Color in Higher Education: Turbulent Past, Promising Future, Women of Color in Higher Education: Contemporary Perspectives and Changing Directions.
ch. 1. Undergraduate institutions that foster black scientists / Frances K. Stage, Ginelle John, Steven M. Hubbard -- ch. 2. African-American, academically gifted, millennial students in STEM disciplines at historically black colleges and universities (HBCUs) : factors that impact successful degree completion / Chance W. Lewis, Fred A. Bonner, Delores Rice, Helene E. Cook, Mary V. Alfred, Felecia M. Nave, Sherri S. Frizell -- ch. 3. African American males in the Meyerhoff scholars program : outcomes and processes / Kenneth I. Maton, Freeman A. Hrabowski, Shauna A. Pollard -- ch. 4. The relationship between academic self-concept and career self-efficacy among African-American males in STEM disciplines at two historically black colleges and universities : an exploratory study / Lamont A. Flowers, James L. Moore, Lawrence O. Flowers, Morris J. Clarke -- ch. 5. Postsecondary educational aspirations and expectations among school-age black males : monitoring the future of black men in STEM fields / Ivory A. Toldson, Brianna P. Lemmons -- ch. 6. Black men in the STEM fields at historically black colleges and universities / Marybeth Gasman -- ch. 7. Reflecting and defying tradition : African-American women in STEM / Lindsey E. Malcom, Shirley M. Malcom -- ch. 8. Black women faculty at historically black colleges and universities : perspectives for a national imperative / Kelly M. Mack, Claudia M. Rankins, Cynthia E. Winston -- ch. 9. Successful PHD pathways to advanced STEM careers for black women / Janet C. Rutledge, Wendy Y. Carter-Veale, Renetta G. Tull -- ch. 10. Sense of belonging and African-American student success in STEM : comparative insights between men and women / Terrell L. Strayhorn -- ch. 11. Maximizing returns on public investments : mentoring African American males in STEM disciplines / P. Gayle Harris Watkins, Wynetta Y. Lee -- ch. 12. What type of institutions are successful at replicating the diversity of the full-time student population in the pool of bachelor's degrees awarded for STEM-disciplines? / Rhonda Vonshay Sharpe -- ch. 13. African American faculty in science and engineering : the illusion of inclusion / Cheryl B. Leggon -- ch. 14. Future faculty/research scientist mentoring program : proven coping strategies for successful matriculation of African Americans in computing science doctoral programs / LaVar J. Charleston, Jerlando F.L. Jackson -- ch. 15. Ten in 10 : a reflective examination of how a university in the south graduated 10 African American computer science Ph.D.s in 10 years / Juan E. Gilbert -- ch. 16. STEM blind spots : moving beyond stock stories and folktales / William F. Tate, Henry T. Frierson.
Keywords: African American college students; African Americans -- Education (Higher)